Answer:
C. -4a + 22b
Step-by-step explanation:
12a + 26b -4b – 16a
= 12a – 16a + 26b – 4b
= -4a + 22b
Answer:
7/8
Step-by-step explanation:
because 1 - ⅛ = 7/8. which would mean the answer is 7/8
Answer:
25.0
Step-by-step explanation:
50/2 = 25
25.00
snnej nsnsns
Answer:
17= addition
18 = 27
Let's solve your equation step-by-step.
43x−4=5−x
Step 1: Simplify both sides of the equation.
43x−4=5−x
43x+−4=5+−x
43x−4=−x+5
Step 2: Add x to both sides.
43x−4+x=−x+5+x
73x−4=5
Step 3: Add 4 to both sides.
73x−4+4=5+4
73x=9
Step 4: Multiply both sides by 3/7.
(37)*(73x)=(37)*(9)
x=277
Answer:
x=277